Term Structure Examination of Indonesian Money Market: Some Efficiency Issue - Budi Nugroho, Anggoro (School of Business and Management Institut Teknologi Bandung, 2011)
This paper examines efficiency of Indonesian term structure as imposed by the country’s central bank. The rate, widely understood as the Bank Indonesia (BI) Rate varying from 30-day, 60-day, and 180-day, usually stated as the plain-vanilla cost of capital of interbank debt financing depending on their time length. In general, this rate will consequently impact various other sorts of interest rates in the country’s debt market as a whole. When dealing with market efficiency, statistical inference shows that short-term BI Rate’s is not the best predictor of its long-term one due to some uncertain asymmetric information. This finding may lead to further adjustment in risk management strategy for hedging with interest rate. Keywords: term structure, risk premia, expectation hypothesis (EH), market efficiency, cointegration, volatility spillover, expansionary monetary policy